2007
DOI: 10.3132/dvdr.2007.053
|View full text |Cite
|
Sign up to set email alerts
|

The role of fenofibrate in clinical practice

Abstract: PPARα is critical to lipid metabolism in the liver. Recent findings which showed that pioglitazone, a PPARγ agonist with weak PPARα activity, improved fatty liver disease in patients with non-alcoholic steatohepatitis (NASH) and metabolic syndrome or type 2 diabetes have prompted interest in whether more potent PPARα agonists, such as fenofibrate, may have a role in the management of non-alcoholic fatty liver disease (NAFLD). The combination of fenofibrate and a statin is well tolerated, with no apparent incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 52 publications
1
34
0
Order By: Relevance
“…For example, metformin and α-lipoic acid prevent hepatic steatosis by inhibiting SREBP-1c production [29,40]. Fenofibrate has beneficial effects on metabolic syndrome by downregulating multiple target genes involved in the pathogenesis of hepatic steatosis [41][42][43]. Recent studies show that fenofibrate induces CREBH production to a level comparable with that observed under fasting conditions [44].…”
Section: Discussionmentioning
confidence: 94%
“…For example, metformin and α-lipoic acid prevent hepatic steatosis by inhibiting SREBP-1c production [29,40]. Fenofibrate has beneficial effects on metabolic syndrome by downregulating multiple target genes involved in the pathogenesis of hepatic steatosis [41][42][43]. Recent studies show that fenofibrate induces CREBH production to a level comparable with that observed under fasting conditions [44].…”
Section: Discussionmentioning
confidence: 94%
“…The half-life of fenofibrate has been reported to be 20 h in individuals with normal renal functions, and the level of fenofibrate required to achieve IC 50 for MCL is within the therapeutic range that is used to treat hyperlipidemia. [43][44][45][46] In light of the excellent safety, tolerability and affordability of fenofibrate, there is merit in investigating the possibility of extending the clinical use of fenofibrate, either as a sole agent or in combination with conventional chemotherapy, in the treatment of MCL.…”
Section: Minomentioning
confidence: 99%
“…Fenofibrate, a PPARα agonist, can specifically bind to PPARα and activate expression of numerous genes participating in fatty acid oxidation, control of triglycerides and cholesterol metabolism (9,10). Fenofibrate, therefore, was very effective to the nonalcoholic fatty liver diseases by modulating lipid metabolic enzymes such as fatty acid transport protein, fatty acid binding protein, long chain acyl-CoA dehydrogenase and acyl-CoA oxidase (11).…”
Section: Introductionmentioning
confidence: 99%